A Global Comparative Analysis of the Global Survey of Business Ethics - Rossouw, Gedeon Josua (2011)
This article concludes this special issue of the Journal of Business Ethics that focussed on the Global Survey of Business Ethics as field of Training, Teaching and Research. The article provides a comparative global analysis of the findings in the eight world regions that participated in this global survey viz. Central Asia, East Asia, Europe, Latin America, North America, Oceania, South and South-East Asia, and Sub-Saharan Africa. The eight regions are compared with regard to their findings on the terminology used to refer to Business and Economic Ethics, the prevalence of Business and Economic Ethics, themes covered in training and teaching programs on Business and Economic Ethics, themes covered in Business and Economic Ethics research, and major business ethical issues that are foreseen over the next 5 years. Broad patterns, continuities and discontinuities that emerged in a comparison across the eight regions are identified and discussed. Finally, the article is concluded by identifying some crucial issues for the further development of the field of Business Ethics.
Keywords: Global comparison; Research; Training; Teaching; Economic Ethics; Business Ethics